Genomic Characterization of Extended-Spectrum Cephalosporin-Resistant Salmonella enterica in the Colombian Poultry Chain - Castellanos, Luis Ricardo; van der Graaf-van Bloois, Linda; Donado-Godoy, Pilar; León, Maribel; Clavijo, Viviana; Arévalo, Alejandra; Bernal, Johan F.; Mevius, Dik J.; Wagenaar, Jaap A.; Zomer, Aldert; Hordijk, Joost (Frontiers in Microbiology, 2018)
Salmonella enterica serovars have been isolated from Colombian poultry. The aim of this study was to investigate the diversity of ESBL/pAmpC genes in extended-spectrum cephalosporin resistant Salmonella enterica and the phylogeny of ESBL/pAmpC-carrying Salmonella using Whole Genome Sequencing (WGS). A total of 235 cefotaxime resitant Salmonella isolates, obtained between 2008 and 2013 from broiler farms, slaughterhouses and retail, were included. Isolates were screened by PCR for ESBL/pAmpC genes. Gene and plasmid subtyping and strain Multi Locus Sequence Typing was performed in silico for a selection of fully sequenced isolates. Core-genome-based analyses were performed per ST encountered. blaCMY was carried in 168 isolates, 52 carried blaCTX-M, 7 blaSHV, 5 a combination of blaCMY-blaSHV and 3 a combination of blaCMY-blaCTX-M. WGS characterization of 36 selected strains showed plasmid-encoded blaCMY-2 in 21, blaCTX-M-165 in 11 and blaSHV-12 in 7 strains. These genes were mostly carried on IncI1/ST12, IncQ1 and IncI1/ST231 plasmids, respectively. Finally, 17 strains belonged to S. Heidelberg ST15, 16 to S. Paratyphi B variant Java ST28, 1 to S. Enteritidis ST11, 1 to S. Kentucky ST152 and 1 to S. Albany ST292. Phylogenetic comparisons with publicly available genomes showed separate clustering of Colombian S. Heidelberg and S. Paratyphi B var. Java. In conclusion, resistance to extended-spectrum cephalosporins in Salmonella from Colombian poultry is mainly encoded by blaCMY-2 and blaCTX-M-165 genes. These genes are mostly associated with IncI1/ST12 and IncQ1 plasmids, respectively. Evolutionary divergence is observed between Colombian S. Heidelberg and S. Paratyphi B var. Java and those from other countries.